2009
DOI: 10.1359/jbmr.081105
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations in SQSTM1 Detected in Affected Tissues From Patients With Sporadic Paget's Disease of Bone

Abstract: Paget's disease of bone (PDB) is a focal disorder of bone remodeling that leads to overgrowth of affected bone, with rare progression to osteosarcoma. Extensive studies of familial PDB showed that a majority of cases harbor germline mutations in the Sequestosome1 gene (SQSTM1). In contrast, little is known about the mutational status of SQSTM1 in sporadic PDB. We hypothesized that somatic SQSTM1 mutations might occur in the affected tissues of sporadic PDB and pagetic osteosarcoma. We used laser capture microd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 47 publications
(100 reference statements)
2
29
1
Order By: Relevance
“…In this context, the presence of somatically acquired SQSTM1 mutations in the pagetic bone cannot be excluded, even though this hypothesis remains controversial and probably restricted to a limited number of patients. (39,40) We and others have previously evidenced an association between PDB and animal-related factors, as well as a significantly higher prevalence of the disease in rural than in urban districts. (26,(41)(42)(43) In this study, we also demonstrated that patients reporting persistent animal contacts for at least 10 years before the onset of disease have an increased number of affected skeletal sites and an increased prevalence of polyostotic disease.…”
Section: Discussionmentioning
confidence: 83%
“…In this context, the presence of somatically acquired SQSTM1 mutations in the pagetic bone cannot be excluded, even though this hypothesis remains controversial and probably restricted to a limited number of patients. (39,40) We and others have previously evidenced an association between PDB and animal-related factors, as well as a significantly higher prevalence of the disease in rural than in urban districts. (26,(41)(42)(43) In this study, we also demonstrated that patients reporting persistent animal contacts for at least 10 years before the onset of disease have an increased number of affected skeletal sites and an increased prevalence of polyostotic disease.…”
Section: Discussionmentioning
confidence: 83%
“…7 RANKL mutations as found in patients with osteoclast-poor osteopetrosis (derived from data presented in [33]). The single amino acid substitution M199K is in a highly conserved domain, the deletion 145-177 removes part of a region known to be essential for biological activity and the deletion V277WFx5 removes the trimerisation domain within p62 in bone cells while none were observed in peripheral blood cells from the same patients [95]; no somatic P392L mutations were identified in the second study [96]. While this indicates that somatic mutations in p62 may occur, but are not essential to develop PDB, it does not exclude the possibility that somatic mutations in other, as yet unidentified, PDB-associated genes may trigger the focal increase in remodelling.…”
Section: Loss-of Function Mutations In Ranklmentioning
confidence: 99%
“…The findings of this study suggest that somatic mutations for SQSTM1 ⁄ p62 are not commonly present in pagetic bones, but a contemporary study reveals somatically acquired SQSTM1 ⁄ p62 mutations in the affected bone and tumour samples from sporadic PDB cases and pagetic osteosarcoma, suggesting to consider such a disease as fitting more closely with the cancer model of somatically acquired mutations, acquired throughout life, occurring at the site of the disease [26]. Thus, PDB may provide a new model by which mutations somatically acquired over the life of the individual are linked to the disease phenotype.…”
Section: Possible Disadvantagesmentioning
confidence: 75%
“…Several authors have suggested that paramyxoviral infection may reproduce some features of PDB and the following findings have been considered to sustain a viral hypothesis in the PDB pathogenesis: (i) paramyxoviral-like nuclear inclusions have been commonly found in pagetic osteoclasts [24,25]; (ii) mRNAs or proteins from measles, canine distemper and respiratory syncytial viruses have been detected in samples from patients with PDB [26][27][28][29][30][31], but not in controls; (iii) infection with paramyxoviruses enables the occurrence of Paget-like changes in osteoclasts. Unfortunately, many other reports have not replicated similar findings in their analysed series [32][33][34][35].…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation